Molybdenum sulfide / carbon composite material with gradient structure as well as preparation method and application of molybdenum sulfide / carbon composite material

By preparing a gradient-structured molybdenum sulfide/carbon composite material, the problems of low conductivity and poor cycle stability of molybdenum sulfide in sodium-ion batteries were solved, and a high specific surface area and excellent electrochemical performance were achieved.

CN120774465APending Publication Date: 2025-10-14QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510974983.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

Existing molybdenum sulfide materials have problems such as low conductivity, poor cycle stability, and low specific surface area in sodium ion batteries, resulting in poor electrochemical reaction performance.

Method used

A gradient-structured molybdenum sulfide/carbon composite material is prepared by vacuum impregnation and calcination to form a gradient pore structure with expanding diameter from the inside to the outside. Phosphomolybdic acid is combined as a molybdenum source to ensure that molybdenum sulfide is evenly distributed in the carbon ball carrier.

Benefits of technology

The specific surface area and ion transport channels of the material are improved, the aggregation problem of the negative electrode material is alleviated, the conductivity and cycle stability are enhanced, and a larger capacity and faster reaction kinetics are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120774465A_ABST
    Figure CN120774465A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium-ion batteries, and relates to a sodium-ion battery negative electrode material, in particular to a molybdenum sulfide / carbon composite material with a gradient structure and a preparation method and application thereof. The preparation method comprises the following steps: uniformly stirring resorcinol, formaldehyde and tetrapropoxysilane under an alkaline condition to obtain phenolic resin / silicon nanospheres; calcining again to obtain crystalline carbon / silicon dioxide nanospheres; then selectively etching to remove the silicon dioxide component to obtain a three-dimensional carbon sphere carrier with a gradient pore structure; mixing the three-dimensional carbon sphere carrier with a sulfur source and phosphomolybdic acid in a solution, and obtaining a MoS2 (at) C precursor by adopting a vacuum impregnation growth method; and carrying out secondary calcination on the MoS2 (at) C precursor under an inert atmosphere condition to obtain the MoS2 (at) C / MoS composite material. The molybdenum sulfide / carbon composite material prepared by the invention has a unique structure, so that the molybdenum sulfide / carbon composite material has good electrochemical stability, excellent rate capability, high specific capacity, large specific surface area and more reaction sites when being used as a negative electrode material of a sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of sodium ion batteries, and relates to a negative electrode material of a sodium ion battery, in particular to a gradient-structured molybdenum sulfide / carbon composite material and a preparation method and application thereof. BACKGROUND

[0002] The information disclosed in this BACKGROUND section is only for the purpose of increasing the understanding of the general background of the application and does not necessarily constitute an admission by the patent applicant(s) that this information constitutes prior art.

[0003] Molybdenum sulfide has excellent performances such as rich active sites, simple preparation method, strong electrochemical reversibility and high specific capacity, and has a wide application in electrode materials. However, the traditional molybdenum sulfide has defects such as low electrical conductivity, poor cycle stability and low specific surface area, which limit the electrochemical reaction. In order to solve the defects of the current molybdenum sulfide, various structures with unique morphology can be designed and synthesized, and the carbon material can be compounded. However, the inventors have found that the negative electrode material prepared at present still has problems such as simple internal structure, low capacity and poor cycle stability. SUMMARY

[0004] In order to solve the defects of the prior art, the purpose of the present application is to provide a gradient-structured molybdenum sulfide / carbon composite material and a preparation method and application thereof. The molybdenum sulfide / carbon composite material prepared by the present application has a unique structure, so that it has good electrochemical stability, excellent rate performance, high specific capacity, large specific surface area and more reaction sites as a negative electrode material of a sodium ion battery.

[0005] In order to achieve the above-mentioned purpose, the technical scheme of the present application is as follows: In a first aspect, a preparation method of a gradient-structured molybdenum sulfide / carbon composite material comprises the following steps: stirring uniformly resorcinol, formaldehyde and tetrapropoxysilane (TPOS) under alkaline conditions to obtain a phenolic resin / silica nanosphere; carrying out primary calcination on the phenolic resin / silica nanosphere in an inert atmosphere to obtain a crystallized carbon / silica nanosphere; carrying out selective etching on the phenolic resin / silica nanosphere to remove the silica component, so as to obtain a three-dimensional carbon sphere carrier with a gradient pore structure; mixing the three-dimensional carbon sphere carrier with a sulfur source and phosphomolybdic acid in a solution, and using a vacuum impregnation growth method to obtain a MoS2@C precursor; carrying out secondary calcination on the MoS2@C precursor under an inert atmosphere, and the gradient-structured molybdenum sulfide / carbon composite material is obtained.

[0006] The present invention uses resorcinol and formaldehyde to prepare a phenolic resin. Tetrapropoxysilane is added and hydrolyzed under alkaline conditions to produce organosilicon. The large number of propoxy groups in the organosilicon allows for better fusion between the organosilicon and the phenolic resin, thereby forming phenolic resin / silicon nanospheres. During the phenolic resin / silicon nanosphere formation process, the tetrapropoxysilane undergoes hydrolysis, condensation, and self-assembly within the nanospheres, forming an inward-to-outward expanding structure. During the primary calcination and pyrolysis process, the organosilicon decomposes to form silica, leaving its skeleton largely unchanged. Therefore, the silica serves as a support material, maintaining the nanosphere structure of the overall composite material. Finally, the silica component is removed by selective etching to obtain three-dimensional carbon spheres. Because the original silica component retains the inward-to-outward expanding structure of the organosilicon within the nanospheres, removal of the silica component results in the three-dimensional carbon spheres forming an inward-to-outward expanding gradient mesoporous structure (referred to as a gradient pore structure), thereby forming a three-dimensional carbon sphere carrier with a gradient pore structure.

[0007] The present invention uses the three-dimensional carbon sphere carrier to load molybdenum sulfide, and controls the structure of the loaded molybdenum sulfide through the gradient pore structure of the three-dimensional carbon sphere carrier, so that the molybdenum sulfide nanosheets self-assemble in the gradient pore structure to form a gradient structure with an expanded diameter from the inside to the outside, and at the same time, gaps are left between the molybdenum sulfide nanosheets and between the molybdenum sulfide and the carbon material. The gradient structure has a large specific surface area and space, which can provide abundant reaction sites. Moreover, the gaps between the gradient molybdenum sulfide and the carbon spheres provide faster ion transmission channels and more free space to accommodate volume expansion. Compounding with carbon materials is the main way to alleviate the aggregation of negative electrode materials and improve conductivity. In addition, a rationally designed gradient structure can accelerate the reaction kinetics of sodium ions and prevent the occurrence of polarization reactions. Therefore, the nanocomposite material provided by the present invention can improve the transfer and diffusion of electrons and ions in sodium ion batteries and provide a larger capacity, showing excellent cycle stability, rate performance and sodium storage performance.

[0008] However, research has found that due to the small pores in the gradient pore structure of the three-dimensional carbon sphere support, it is difficult to fill the gradient pore structure of the three-dimensional carbon sphere support with conventional molybdenum sources such as ammonium molybdate during the preparation process, making it difficult to fill the gradient pore structure with molybdenum disulfide as expected to form the desired structure. The present invention further discovered that when phosphomolybdic acid is used as the molybdenum source, it can fill the gradient pore structure with the molybdenum source and form the desired gradient structure. In addition, no phosphorus is left during the subsequent secondary calcination process, thus forming a gradient molybdenum sulfide / carbon composite material.

[0009] On the other hand, a gradient-structured molybdenum sulfide / carbon composite material is obtained by the above preparation method.

[0010] The third aspect is the application of the above-mentioned gradient structured molybdenum sulfide / carbon composite material in the negative electrode material of sodium ion battery.

[0011] In a fourth aspect, a negative electrode for a sodium ion battery comprises an active material, a conductive agent, a binder and a current collector, wherein the active material is the above-mentioned nanocomposite material with a gradient structure.

[0012] In a fifth aspect, a sodium ion battery comprises a positive electrode, a negative electrode and a secondary electrolyte, wherein the negative electrode is the negative electrode of the sodium ion battery described above.

[0013] The beneficial effects of the present invention are: 1. The nanocomposite material with a gradient structure provided by the present invention contains transition metal sulfide and carbon material. Due to the synergistic effect of the two components, the material has more active sites, which is more conducive to electrochemical reaction.

[0014] 2. The present invention adopts vacuum impregnation method and calcination and other heat treatment methods to prepare molybdenum sulfide / carbon nanocomposite materials with gradient structure. The synthesis process is simple, easy to operate, green and environmentally friendly, and has low energy consumption.

[0015] 3. The gradient-structured nanocomposite material prepared by the present invention has a unique gradient structure, a large specific surface area, and high porosity, etc., which provides sufficient ion transmission channels and free space, effectively buffers volume expansion, shortens the diffusion path of ions, promotes the transmission and transport of ions, and promotes the progress of electrochemical reactions. 4. The nanocomposite material with a gradient structure provided by the present invention, through compounding with carbon materials, alleviates the problem of negative electrode material aggregation and improves its own conductivity.

[0016] 5. The gradient structure nanocomposite material provided by the present invention greatly improves the theoretical capacity of the composite material due to the presence of transition metal sulfide (molybdenum sulfide), facilitates charge transfer and provides a larger capacity.

[0017] 6. The sodium ion battery prepared with the gradient structure nanocomposite material provided by the present invention as the negative electrode material exhibits excellent rate performance and cycle stability in electrochemical tests. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0019] Figure 1 Electron micrographs of the gradient pore carbon sphere carrier prepared in Example 1 of the present invention, (a) is a scanning electron micrograph (SEM); (b) is a transmission electron micrograph (TEM); Figure 2Electron micrographs of MoS2@MC-I with a gradient structure prepared in Example 2 of the present invention, (a) is a scanning electron micrograph (SEM); (b) is a transmission electron micrograph (TEM); Figure 3 Electron micrographs of MoS2@MC-II with a gradient structure prepared in Example 3 of the present invention, (a) is a scanning electron micrograph (SEM); (b) is a transmission electron micrograph (TEM); Figure 4 The gradient structure MoS2@MC-II composite material prepared in Example 3 of the present invention was –1 The cycle performance curve diagram below; Figure 5 This is a rate performance diagram of the gradient-structured MoS2@MC-II composite material prepared in Example 3 of the present invention; Figure 6 The gradient structure MoS2@MC-II composite material prepared in Example 3 of the present invention was –1 The first three cycles of charge and discharge curves below; Figure 7 Electron micrographs of MoS2@MC-III with a gradient structure prepared in Example 4 of the present invention, (a) is a scanning electron micrograph (SEM); (b) is a transmission electron micrograph (TEM); Figure 8 XRD patterns of the gradient-structured MoS2@MC composite materials prepared in Examples 2, 3, and 4 of the present invention, where the ordinate is the relative diffraction intensity and the abscissa is the 2θ diffraction angle. DETAILED DESCRIPTION

[0020] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs.

[0021] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.

[0022] The negative electrode materials currently prepared for use in sodium ion batteries still have problems such as simple internal structure, low capacity and poor cycle stability. The present invention proposes a gradient-structured molybdenum sulfide / carbon composite material and its preparation method and application.

[0023] A typical embodiment of the present invention provides a method for preparing a gradient-structured molybdenum sulfide / carbon composite material, comprising the following steps: Resorcinol, formaldehyde, and tetrapropoxysilane (TPOS) were stirred evenly under alkaline conditions to obtain phenolic resin / silicon nanospheres; calcining the phenolic resin / silicon nanospheres in an inert atmosphere to obtain crystallized carbon / silicon dioxide nanospheres; The phenolic resin / silica nanospheres are selectively etched to remove the silica component, thereby obtaining a three-dimensional carbon sphere carrier with a gradient pore structure. The three-dimensional carbon sphere carrier is mixed with a sulfur source and phosphomolybdic acid in a solution, and a MoS2@C precursor is obtained by a vacuum impregnation growth method; Under inert atmosphere, the MoS2@C precursor is subjected to secondary calcination to obtain the product.

[0024] The vacuum impregnation method described in the present invention refers to a process in which the environment in which the reactants are located is vacuumed in a closed system, the solvent is evaporated at high temperature, and the original mixture is reacted under a certain temperature and pressure. The nanocomposite material with a gradient structure synthesized by the vacuum impregnation method of the present invention has relatively uniform size and good crystallinity. In addition, there is a synergistic effect between molybdenum sulfide and carbon material, which increases the active sites of the material and makes it have excellent rate performance and cycle stability. At the same time, due to its unique gradient structure, it has the characteristics of large specific surface area and high porosity, provides sufficient ion transmission channels and free space to accommodate volume expansion, alleviates the aggregation problem of negative electrode materials and improves its own conductivity and sodium storage performance.

[0025] The alkaline conditions described herein refer to alkaline solutions, which can be aqueous ammonia, sodium hydroxide, potassium hydroxide, or the like. In some embodiments, resorcinol and formaldehyde are added to an alkaline alcohol solution and mixed evenly, followed by the dropwise addition of tetrapropoxysilane. The reaction is then continued to yield phenolic resin / silicon nanospheres. Specifically, the reaction is continued for 22 to 26 hours. Specifically, the reaction is continued for 22 to 26 hours. Specifically, the reaction temperature for obtaining the phenolic resin / silicon nanospheres is 20 to 40°C. Specifically, the purification process can employ solid-liquid separation, which can be performed by filtration, centrifugation, or the like.

[0026] In some embodiments, the molar ratio of resorcinol, formaldehyde, and tetrapropoxysilane is 1:1.7-2.0:9.0-10.0.

[0027] The inert atmosphere of the present invention refers to an inert gas atmosphere such as nitrogen, helium, neon, or argon, and is generally a nitrogen atmosphere or an argon atmosphere. In some embodiments, the primary calcination temperature is 750-850°C.

[0028] In some embodiments, the selective etching agent is a hydrofluoric acid solution. The hydrofluoric acid solution can selectively etch away the silicon dioxide component. Specifically, the concentration of the hydrofluoric acid solution is 4-6 wt%.

[0029] In some embodiments, the three-dimensional carbon sphere support is added to water and mixed evenly. A sulfur source is added and heated to 45-55°C and mixed evenly. Phosphomolybdic acid is then added and mixed evenly, followed by vacuum impregnation growth. Specifically, the vacuum impregnation growth temperature is 60-80°C. Specifically, the vacuum impregnation growth time is overnight, typically 8-14 hours.

[0030] In some embodiments, the secondary calcination temperature is 550-650° C., and the secondary calcination time is 1.5-2.5 h.

[0031] In some embodiments, the addition ratio of the three-dimensional carbon sphere support to the sulfur source and phosphomolybdic acid is 1:0.085 to 0.254, calculated as a molar ratio of carbon support to molybdenum sulfide. When the molar ratio of carbon support to molybdenum sulfide is 1:0.120 to 0.254, it is possible to ensure that the gradient pore structure of the three-dimensional carbon sphere support is fully filled with molybdenum sulfide.

[0032] The preferred steps of the present invention are: (1) Anhydrous ethanol and deionized water were uniformly mixed on a magnetic stirrer at 30°C and stirred until a clear solution was formed; (2) adding the clear and transparent solution obtained in step (1) to an aqueous ammonia solution and stirring the mixture uniformly. Thereafter, adding resorcinol and formaldehyde to the mixed solution; (3) Tetrapropoxysilane is added dropwise to the mixed solution obtained in step (2), and stirring is continued at 30° C. to mix the mixture evenly; then, the product is centrifuged to obtain resin / silicon solid composite microspheres.

[0033] (4) The sample obtained in step (3) was carbonized at 800° C. under a nitrogen atmosphere. Subsequently, the silicon dioxide was selectively etched away to obtain a carbon sphere support.

[0034] (5) Add the carbon support obtained in step (4) to deionized water. After mixing, add thiourea. After stirring at 50°C, add phosphomolybdic acid and continue stirring. Then, dry in a vacuum drying oven overnight. (6) The precursor obtained in step (5) was heated to 600° C. in a tube furnace under an argon atmosphere and maintained at this temperature for 2 hours to obtain the target product.

[0035] Specifically, in step (1), the preferred stirring time is 0.5 h.

[0036] In step (2), the stirring time is 0.5 to 2 h, and the further preferred condition is stirring at 30° C. for 1 h.

[0037] In step (3), the centrifugation conditions are to use deionized water and anhydrous ethanol, and centrifuge and wash 3 to 6 times. The centrifugation conditions are preferably to use deionized water for 3 times and anhydrous ethanol for 2 times.

[0038] In step (4), the selective etching condition is a hydrofluoric acid aqueous solution, and the condition is preferably a 5% wt HF aqueous solution.

[0039] In step (5), the vacuum drying oven is dried at a temperature of 60-80 ° C for 10-14 h, and the drying temperature is preferably 70 ° C for 12 h.

[0040] In step (6), the calcination temperature is 550-600 ° C, and the optimal temperature is more preferably 600 ° C.

[0041] Another embodiment of the present invention provides a gradient-structured molybdenum sulfide / carbon composite material obtained by the above-mentioned preparation method.

[0042] In some embodiments, the average inner diameter of the gradient pore structure in the three-dimensional carbon sphere carrier is 9-10 nm, and the specific surface area is greater than 1022 m 2 g -1 .

[0043] In some embodiments, the nanospheres have a diameter of 300-400 nm.

[0044] A third embodiment of the present invention provides an application of the above-mentioned gradient-structured molybdenum sulfide / carbon composite material in a negative electrode material for a sodium ion battery.

[0045] A fourth embodiment of the present invention provides a sodium ion battery negative electrode, comprising an active material, a conductive agent, a binder and a current collector, wherein the active material is the above-mentioned nanocomposite material with a gradient structure.

[0046] In some embodiments, the mass ratio of the active material, the conductive agent, and the binder is 65-80:15-30:10-15.

[0047] In some embodiments, the conductive agent is acetylene black, Ketjen black, or carbon nanotubes, etc. Ketjen black has higher conductivity, and using Ketjen black as a conductive agent can reduce the amount of conductive agent used.

[0048] In some embodiments, the binder is polyvinylidene fluoride, sodium carboxymethyl cellulose, or polyacrylic acid. When polyvinylidene fluoride is used as the binder, an organic solvent is required to disperse the materials. When sodium carboxymethyl cellulose or polyacrylic acid is used as the binder, water is required to disperse the materials. In the present invention, sodium carboxymethyl cellulose is preferably used as the binder.

[0049] A fifth embodiment of the present invention provides a sodium ion battery, comprising a positive electrode, a negative electrode and a secondary electrolyte, wherein the negative electrode is the negative electrode of the sodium ion battery described above.

[0050] In some embodiments, the secondary electrolytes used are NP-005 and NC-034. The NP-005 electrolyte is sodium hexafluorophosphate, and the solvent is diglyme; the NC-034 electrolyte is sodium perchlorate, and the solvent is a mixed solution of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate (volume ratio of 1:1:1).

[0051] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments and comparative examples.

[0052] Example 1 A method for preparing mesoporous carbon spheres with gradient pores comprises the following steps: In a typical synthesis process, 70 mL of anhydrous ethanol and 12 mL of deionized water were mixed uniformly on a magnetic stirrer at 30°C. Then, 4 mL of aqueous ammonia solution was added and stirred thoroughly. Resorcinol (0.4 g) and formaldehyde (0.5 mL, 37% wt) were then added to the mixture. After the solids were completely dissolved, 9 mL of tetrapropoxysilane was added dropwise to each of the above mixtures, and stirring was continued at 30°C for 24 hours. Subsequently, the resin / silicon solid composite microspheres were obtained by centrifugation. Carbonization treatment was performed at 800°C under a nitrogen atmosphere. Subsequently, the silica was selectively etched away with a 5 wt% aqueous hydrofluoric acid solution to obtain the gradient pore size carbon sphere support.

[0053] The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images of the mesoporous carbon spheres with gradient pore structure obtained in this example are shown in Figure 2. Figure 1 (a) and Figure 1 (b) Figure 1 The results show that the mesoporous carbon spheres (MC) prepared in this example have obvious gradient pore structure. 2 g –1 The average pore size is about 10 nm.

[0054] Example 2 The carbon support prepared in Example 1 was added to 10 mL of deionized water. After mixing evenly, CS (NH3)2was added. After stirring at 50°C for 1.5 hours, H3PMo 12 O 40 was added and stirring was continued for 2 hours. Subsequently, it was dried in a vacuum drying oven at 70°C overnight. Then, the above precursor was further heated to 600°C at a heating rate of 5°C per minute and kept at this temperature for 2 hours under argon atmosphere to obtain the target product. By adding C and MoS2in a molar ratio of 1:0.085, the composite material MoS2@MC-I was obtained.

[0055] The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the gradient-structured composite material MoS2@MC-I prepared in this example are shown in Figure 2 (a) and Figure 2 (b), Figure 2 (a) shows that the prepared MoS2@MC-I composite material is a nanosphere structure with a diameter of 300-400 nm, and the gradient pore carbon sphere still shows obvious pore structure, Figure 2 (b) shows that the pore structure of the carbon support in the MoS2@MC-I composite material is still obvious, indicating that the molybdenum sulfide material has entered the carbon sphere support pores but has not been completely filled.

[0056] Example 3 The carbon support prepared in Example 1 was added to 10 mL of deionized water. After mixing evenly, CS (NH3)2was added. After stirring at 50°C for 1.5 hours, H3PMo 12 O 40 was added and stirring was continued for 2 hours. Subsequently, it was dried in a vacuum drying oven at 70°C overnight. Then, the above precursor was further heated to 600°C at a heating rate of 5°C per minute and kept at this temperature for 2 hours under argon atmosphere to obtain the target product. By adding C and MoS2in a molar ratio of 1:0.127, the composite material MoS2@MC-II was obtained.

[0057] The gradient-structured composite material MoS2@MC-II obtained in this example was used as a negative electrode material for sodium ion batteries. The negative electrode material was mixed with Ketjen black and sodium carboxymethyl cellulose in a mass ratio of 8:1:1 in deionized water, then coated on a copper foil and vacuum dried to obtain a negative electrode. The positive electrode used was a sodium sheet, and the secondary electrolyte was NP-005, in which the electrolyte was sodium hexafluorophosphate and the solvent was diglyme. A sodium ion battery was assembled.

[0058] The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the gradient-structured composite material MoS2@MC-II prepared in this example are shown in Figure 3(a) and Figure 3 (b) Figure 3 (a) shows that the prepared MoS2@MC-II composite material is a nanosphere structure with a diameter of 300~400 nm, and the gradient pore carbon sphere structure tends to disappear. Figure 3 (b) shows that the carbon support pore structure in the MoS2@MC-II composite material is basically filled, indicating that the molybdenum sulfide material has achieved filling in the gradient pores. However, the material has a porous structure, and the existence of pores is caused by the lamellar structure of molybdenum sulfide. The gradient molybdenum sulfide with pores has sufficient expansion space, which is conducive to alleviating the volume expansion phenomenon during the sodium ion embedding process, which also provides support for its good electrochemical performance. Figure 4 As shown, at 5.0 A g –1 The discharge capacity of the battery is 290.4 mAh g after more than 2500 cycles of charge and discharge at a current density of –1 The results were tested at different current densities from 0.5 to 10 A g –1 The rate performance under Figure 5 As shown, at 0.5, 1.0, 2.0, 4.0, 6.0, 8.0 and 10.0 A g –1 At current densities of 431.8, 408.5, 370.8, 333.8, 311.8, 295.6, and 283.4 mAh g –1 discharge capacity. Figure 6 The MoS2@MC-II composite material was demonstrated to have a current density of 0.1 A g –1 The first three cycles of charge and discharge curves are shown below.

[0059] Example 4 The carbon support prepared in Example 1 was added to 10 liters of deionized water. After mixing, CS (NH3)2 was added. After stirring at 50°C for 1.5 hours, H3PMo 12 O 40 , and continued stirring for 2 hours. Subsequently, the mixture was dried in a vacuum drying oven at 70°C overnight. The precursor was then further heated to 600°C at a heating rate of 5°C per minute and maintained at this temperature for 2 hours under an argon atmosphere to obtain the target product. The composite material, MoS2@MC-III, was obtained by adding MoS2 and C at a molar ratio of 1:0.254.

[0060] The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the gradient structure composite material MoS2@MC-III prepared in this embodiment are shown in FIG. Figure 7 (a) and Figure 7 (b) Figure 7(a) shows that the prepared MoS2@MC-III composite material is a nanosphere structure with a diameter of 300~400 nm, and the surface is covered with lamellar molybdenum sulfide, and the pore structure completely disappears. Figure 7 (b) shows that the MoS2@MC-III composite material has been filled with MoS2 in the gradient pores, and the pores are also surrounded by lamellar MoS2. Figure 8 ) can prove the successful preparation of the three composite materials.

[0061] The gradient-structured MoS2@MC-III composite material obtained in this example was used as a negative electrode material for a sodium ion battery. The negative electrode material, Ketjen black, and sodium carboxymethyl cellulose were added to deionized water at a mass ratio of 7:2:1 and mixed evenly. The mixture was then coated on a copper foil and vacuum-dried to obtain a negative electrode. A sodium sheet was used as the positive electrode, and a sodium ion battery was assembled.

[0062] Example 5 The carbon support prepared in Example 1 was added to 10 ml of deionized water. After mixing, CS (NH3)2 was added. After stirring at 50°C for 1.5 hours, H3PMo 12 O 40 , and continued stirring for 2 hours. Subsequently, the mixture was dried in a vacuum drying oven at 70°C overnight. The precursor was then further heated to 650°C at a heating rate of 5°C per minute and maintained at this temperature for 2 hours under an argon atmosphere to obtain the desired product. The composite material, MoS2@MC-IV, was obtained by adding C and MoS2 at a molar ratio of 1:0.254.

[0063] The composite material obtained in this example is used as a negative electrode material for a sodium ion battery. The negative electrode material, Ketjen black, and sodium carboxymethyl cellulose are added to deionized water at a mass ratio of 8:1:1 and mixed evenly. The mixture is then coated on a copper foil and vacuum dried to obtain a negative electrode. A sodium sheet is used as the positive electrode, and a sodium ion battery is assembled.

[0064] Comparative Example 1 The carbon support prepared in Example 1 was added to 10 ml of deionized water. After mixing, CS (NH 3) 2 was added. After stirring at 50 ° C for 1.5 hours, ammonium molybdate tetrahydrate was added and stirring was continued for 2 hours. Subsequently, it was dried in a vacuum drying oven at 70 ° C overnight. Then, the above precursor was further heated to 600 ° C at a heating rate of 5 ° C per minute and maintained at this temperature for 2 hours under an argon atmosphere to obtain the product. By adding C and MoS 2 at a molar ratio of 1: 0.127.

[0065] The results show that when ammonium molybdate tetrahydrate is used as the molybdenum source, MoS2 cannot be filled into the gradient pore structure of the carbon support.

[0066] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A method for preparing a gradient structured molybdenum sulfide / carbon composite material, characterized in that: The steps include: Resorcinol, formaldehyde and tetrapropoxysilane are stirred evenly under alkaline conditions to obtain phenolic resin / silicon nanospheres; calcining the phenolic resin / silicon nanospheres in an inert atmosphere to obtain crystallized carbon / silicon dioxide nanospheres; The phenolic resin / silica nanospheres are selectively etched to remove the silica component, thereby obtaining a three-dimensional carbon sphere carrier with a gradient pore structure. The three-dimensional carbon sphere carrier is mixed with a sulfur source and phosphomolybdic acid in a solution, and a MoS2@C precursor is obtained by a vacuum impregnation growth method; Under inert atmosphere, the MoS2@C precursor is subjected to secondary calcination to obtain the product.

2. The preparation method according to claim 1, wherein Resorcinol and formaldehyde are added to an alkaline alcohol aqueous solution and mixed evenly, and tetrapropoxysilane is then added dropwise, and the reaction is continued to obtain phenolic resin / silicon nanospheres; Alternatively, the molar ratio of resorcinol, formaldehyde and tetrapropoxysilane is 1:1.7~2.0:9.0~10.

0.

3. The preparation method according to claim 1, wherein The primary calcination temperature is 750~850℃; Alternatively, the etchant for selective etching is a hydrofluoric acid aqueous solution; Alternatively, the temperature of the secondary calcination is 550-650°C, and the time of the secondary calcination is 1.5-2.5 h.

4. The preparation method according to claim 1, wherein The three-dimensional carbon sphere support is added to water and mixed evenly, a sulfur source is added, and the mixture is heated to 45-55° C. and mixed evenly, and then phosphomolybdic acid is added and mixed evenly, followed by vacuum impregnation growth; alternatively, the vacuum impregnation growth temperature is 60-80° C.; alternatively, the vacuum impregnation growth time is overnight; Alternatively, the addition ratio of the three-dimensional carbon sphere carrier to the sulfur source and phosphomolybdic acid is 1:0.085~0.254 or 1:0.120~0.254 based on the molar ratio of the carbon carrier to molybdenum sulfide.

5. A gradient structured molybdenum sulfide / carbon composite material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 4.

6. The molybdenum sulfide / carbon composite material according to claim 5, wherein: The average inner diameter of the gradient pore structure in the three-dimensional carbon sphere carrier is 9-10 nm, and the specific surface area is >1022 m 2 g -1 ; Alternatively, the diameter of the nanospheres is 300~400 nm.

7. Use of the gradient-structured molybdenum sulfide / carbon composite material according to claim 5 or 6 in a negative electrode material for a sodium ion battery.

8. A sodium ion battery negative electrode, comprising an active material, a conductive agent, a binder and a current collector, characterized in that: The active substance is the nanocomposite material with a gradient structure as claimed in claim 5 or 6.

9. The sodium ion battery negative electrode according to claim 8, wherein: The mass ratio of active material, conductive agent and binder is 65~80:15~30:10~15.

10. A sodium ion battery comprising a positive electrode, a negative electrode and a secondary electrolyte, characterized in that: The negative electrode is the sodium ion battery negative electrode according to claim 8 or 9.